The Relationship Career Adaptability on Employee Turnover and Mediation Role of Perceived Overqualification at PT. Kimia Farma Diagnostika - Wibowo, Winastanto; Suhariadi, Fendy; Dinda, Fiona Niska (RSF Conference Series: Business, Management and Social Sciences, 2024)
The goal of this study was to identify the effect of career adaptability on turnover intention and to analyze the mediation role of perceived overqualification on employees of PT. Kimia Farma Diagnostika. This study involved 80 respondents with a quantitative approach and SEM-PLS multivariate analysis method for data analysis. This research found that career adaptability showed a positive and significant effect on turnover intention. In addition, it was also found that perceived overqualification partially mediated the relationship between career adaptability and turnover intention. The practical implications of this study are to provide insight to the management of PT. Kimia Farma Diagnostika to design more effective employee retention strategies. Further research is recommended to expand the scope of analysis at the organizational level, consider additional moderating variables, and address existing limitations. Thus, this study makes an important contribution to understanding and addressing employee retention issues in these companies.